2017
DOI: 10.1021/acsami.7b07058
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Measurement of Electrosorption-Induced Deformation Reveals the Importance of Micropores in Hierarchical Carbons

Abstract: Dimensional changes in carbon-based supercapacitor electrodes were investigated using a combination of electrochemical dilatometry and in situ small-angle X-ray scattering. A novel hierarchical carbon material with ordered mesoporosity was synthesized, providing the unique possibility to track electrode expansion and shrinkage on the nanometer scale and the macroscopic scale simultaneously. Two carbons with similar mesopore structure but different amounts of micropores were investigated, employing two differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(61 citation statements)
references
References 29 publications
(69 reference statements)
3
52
0
Order By: Relevance
“…This result is related to the combination of total ion concentration (cations and anions) change during charging with a higher amount of micropores and the electron/hole doping causing the elongation of C-C bonding. 233 A further study showed that in the ionic liquid system, with a different size of anions, the organization of ions confined in nanopores varies. 234 This can be observed by dilatometry because the strain of pores is sensitive to ion adsorption/desorption, orientation, and transportation.…”
Section: Other Ex Situ and In Situ Characterization Techniquesmentioning
confidence: 99%
“…This result is related to the combination of total ion concentration (cations and anions) change during charging with a higher amount of micropores and the electron/hole doping causing the elongation of C-C bonding. 233 A further study showed that in the ionic liquid system, with a different size of anions, the organization of ions confined in nanopores varies. 234 This can be observed by dilatometry because the strain of pores is sensitive to ion adsorption/desorption, orientation, and transportation.…”
Section: Other Ex Situ and In Situ Characterization Techniquesmentioning
confidence: 99%
“…They should however not influence the adsorption data from the mesopores at larger relative pressures A detailed description of the sample synthesis is given in Ref. (Koczwara et al 2017).…”
Section: B1: Synthesis Of the Carbon Samplementioning
confidence: 99%
“…Calculations with a simplified, analytical model of the "bridged phase" are performed to elucidate numerical results and provide comparison to traditional characterization approaches such as the Kelvin-Cohan (Neimark et al 2003) equation. Predictions from the numerical results are compared with experimentally measured adsorption isotherms from CMK-3-like carbon materials (Koczwara et al 2017) using nitrogen at 77 K and n-pentane at 290 K.…”
Section: Introductionmentioning
confidence: 99%
“…Although the hydrogen adsorption and desorption inside the porosity of carbon remain reversible within certain potential limits, this process never is fully reversible and, therefore, consumes additional charges resulting in the reduced energy efficiency of the system at high voltages. To improve the charging performance of carbon electrode materials, the ionic species must be continuously and swiftly transported to/from the carbon/electrolyte interface within the porosity with a minimum amount of free water . The latter factor contributes to the efficient ion packing by appropriate modification of the screening effect due to the presence of a solvent and improves in‐pore conductivity of ionic species …”
Section: Introductionmentioning
confidence: 99%
“…To improve the charging performance of carbon electrode materials, the ionic species must be continuously and swiftly transported to/from the carbon/electrolyte interface within the porosity with a minimum amount of free water. [31,32] The latter factor contributes to the efficient ion packing by appropriate modification of the screening effect due to the presence of a solvent and improves in-pore conductivity of ionic species. [33][34][35][36] In this work, we studied aqueous sodium nitrate (pH ¼ 6.4) with two concentrations of 8.0 and 1.0 m NaNO 3 as electrolytes in carbon/carbon cells.…”
Section: Introductionmentioning
confidence: 99%